Decomposing Welfare Wedges. An Analysis of Welfare Dependence of Immigrants and Natives in Europe - Peter Huber; Doris A. Oberdabernig (Austrian Institute of Economic Research (WIFO), 2014)
We study differences in contributory and non-contributory welfare benefit receipt between immigrants and natives for 16 EU countries. In contrast to previous studies we analyse differences in benefit levels allowing for potentially different takeup rates between immigrants and natives and use Oaxaca-Blinder decompositions to discuss residual welfare dependence. Results point to substantial heterogeneity in welfare dependence between countries when not controlling for observed characteristics of immigrants and natives. This is primarily due to different selection into benefits between immigrants and natives and differences in their characteristics (mainly income, personal, and household characteristics). Once this is controlled for, immigrants participate at most equally often in both types of benefits as natives and usually also receive lower or comparable benefit levels.
Keywords: 330; EU countries; immigration; Oaxaca-Blinder decompositions; welfare benefits; Öffentliche Sozialleistungen; Grundbedürfnisse; Soziale Lage; Migranten; Dekompositionsverfahren; EU-Staaten